Periodontitis promotes tumor growth and immune evasion via PD-1/PD-L1 - Suli Wang; Fujiao Nie; Qiuyue Yin; Haoyang Tian; Pizhang Gong; Jinhong Ju; Jiayi Liu; Pishan Yang; Chengzhe Yang (Cancer Immunology, Immunotherapy)
Abstract Background Our study investigated the role of experimental periodontitis on tumor growth, local and systemic immunosuppressive status, and programmed death receptor 1 (PD-1) / programmed death ligand 1 (PD-L1) expression in oral squamous cell carcinoma (OSCC) and prostate cancer. Methods Mouse oral or prostate cancer xenograft models were divided into control, periodontitis and periodontitis + anti-PD-1 groups. Tumor volume and weight were recorded and the levels of relevant immune-suppressive cells and T cells were detected by flow cytometry or immunofluorescence. THP-1 cells were stimulated using conditioned media of LPS-stimulated Cal-27 cells and PD-L1 expression was measured by quantitative real-time PCR, western blotting and immunofluorescence. Tumor specimens from OSCC patients with or without periodontitis were also collected for immunofluorescence. Results Periodontitis significantly promoted tumor volume and weight. Compared to the control, the proportions of tumor-associated macrophages (TAMs), regulatory T cells (Tregs), PD-L1+TAMs and PD-1+CD8+T cells increased, while CD8+T cells decreased in the periodontitis group. Immunofluorescence demonstrated that there was an increase in PD-L1+TAMs and PD-1+CD8+T cells, but a decrease in IFN-γ+CD8+T cells in both xenografts and clinical OSCC samples with periodontitis. In vitro, LPS-stimulated Cal-27 cells had a stronger potential to induce PD-L1 expression in macrophages compared with unstimulated Cal-27 cells. And the promoting effect of periodontitis on tumor growth and immune evasion was significantly attenuated after anti-PD-1 therapy. Conclusion Periodontitis may facilitate tumor growth and immune escape evidenced by the increased immune-suppressive cells and the decreased functional T cells, via enhancing PD-1/PD-L1 expression in the tumor microenvironment.